2021
DOI: 10.1016/j.jsat.2020.108263
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging COVID-19 to sustain regulatory flexibility in the treatment of opioid use disorder

Abstract: The U.S. government declared the opioid epidemic as a national public health emergency in 2017, but regulatory frameworks that govern the treatment of opioid use disorder (OUD) through pharmaceutical interventions have remained inflexible. The emergence of the COVID-19 pandemic has effectively removed regulatory restrictions that experts in the field of medications for opioid use disorder (MOUD) have been proposing for decades and has expanded access to care. The regulatory flexibilities implemented to avoid u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Early findings suggested that the regulatory changes to MOUD access and administration designed to slow the spread of COVID-19 have increased buprenorphine access ( Komaromy et al, 2020 ; Stringer et al, 2021 ), and have not led to increases in adverse events in methadone programs ( Brothers et al, 2021 ; Figgatt et al, 2021 ). Our study findings show that some participants on methadone found receiving take homes more challenging than expected, and others described telemedicine for therapy or buprenorphine treatment as less meaningful and lower quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early findings suggested that the regulatory changes to MOUD access and administration designed to slow the spread of COVID-19 have increased buprenorphine access ( Komaromy et al, 2020 ; Stringer et al, 2021 ), and have not led to increases in adverse events in methadone programs ( Brothers et al, 2021 ; Figgatt et al, 2021 ). Our study findings show that some participants on methadone found receiving take homes more challenging than expected, and others described telemedicine for therapy or buprenorphine treatment as less meaningful and lower quality.…”
Section: Discussionmentioning
confidence: 99%
“…For patient-centered care to be equitable, supports must be in place to ensure those facing structural marginalization can benefit from and participate in shared decision-making. Concrete steps that may have alleviated the destabilizing and unjust experiences described by our participants include: providing cell phones to those who needed them to access telemedicine and online recovery supports, transportation to health services, and expanding clinic hours to allow for social distancing and treatment access flexibility ( Harris et al, 2021 ; Stringer et al, 2021 ). For those newly housed, conducting home visits and active outreach may have identified the destabilizing impacts that changes in a daily routine had for people who were accustomed to daily methadone clinic attendance ( de Vet et al, 2013 ; Kertesz et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…A phone-based MOUD telehealth program was similarly effective in San Francisco ( Mehtani et al, 2021 ). Some academic authors have now called for permanent easement of face to face delivery restrictions on MOUD delivery ( Stringer, Langdon, Mckenzie, Brockmann, & Marotta, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the rates of participants who met the cut-off scores for singular and multiple addictions were relatively consistent with those reported in previous research (Beranuy et al, 2020 ; Grant & Steinberg, 2005 ; Luo et al, 2021 ). Overall, one could conclude that those assessed at higher risk for multiple addictions during the time of the COVID-19 pandemic (in this community online sample) exceeded 40% of the respondents, likely confirming that COVID-19-distress-related effects impact significant increases in addiction presentations (Arora et al, 2021 ; Rubin, 2021 ; Stringer et al, 2021 ).…”
Section: Discussionmentioning
confidence: 53%